Secondary battery and electric device
By using a high-pressure density negative electrode film layer and appropriate negative electrode active material in the negative electrode sheet of the secondary battery, the problem of difficult to take into account both energy density and circulation performance in the prior art is solved, and high energy density and excellent circulation performance and storage performance are achieved.
Patent Information
- Application Number
- CN202311676650.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-07
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-12-07
AI Technical Summary
When existing secondary batteries increase their energy density, it is difficult to take into account the battery's circulation performance; when improving their circulation performance, it often affects the energy density.
By using a high-pressure density negative electrode film layer in the negative electrode sheet, combined with the appropriate liquid absorption rate and tortuosity of the negative electrode active material, the electrolyte is ensured to fully penetrate the negative electrode sheet and reduce the possibility of local polarization.
It achieves the improvement of the battery's cycle performance and storage performance under the premise of high energy density, and extends the battery's service life and storage life.
Smart Images

Figure CN119852533A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a secondary battery and an electrical device. Background Art
[0002] The secondary battery market for energy storage is experiencing a huge boom. Energy density and cycle life are important indicators for energy storage batteries, especially for batteries used in large energy storage power stations. However, the problems faced by existing technologies are: when improving the energy density of energy storage batteries, it is often difficult to take into account the battery's cycle performance; when improving the cycle performance of secondary batteries, the battery's energy density is often affected. Summary of the invention
[0003] The present application is made in view of the above-mentioned problems, and its purpose is to provide a secondary battery and an electrical device, wherein the secondary battery has a high energy density and excellent cycle performance.
[0004] The first aspect of the present application provides a secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer comprises a negative electrode active material, and the compaction density of the negative electrode film layer is greater than or equal to 1.45 g / cm 3 The liquid absorption rate of the negative electrode active material is 30ml / 100g-60ml / 100g; the tortuosity of the negative electrode plate is less than or equal to 6.
[0005] Under the premise of high compaction density, the liquid absorption rate of the negative electrode active material and the tortuosity of the negative electrode plate are controlled within an appropriate range, so that the electrolyte can fully infiltrate the negative electrode plate during repeated lithium insertion and extraction of the negative electrode, reducing the possibility of local polarization, making the current of the negative electrode plate evenly distributed during the cycle, reducing the possibility of side reactions at the negative electrode interface during the cycle, and reducing the impact of the by-products of the side reactions blocking the pores on the cycle performance and storage performance of the battery.
[0006] The negative electrode plate of the secondary battery of the present application has a high compaction density, and the electrolyte can fully infiltrate the negative electrode plate during the circulation process, which can further improve the battery's cycle performance and storage performance while having a high energy density.
[0007] In any embodiment, the compaction density of the negative electrode film layer is 1.5 g / cm 3 -1.6g / cm 3 .
[0008] The compaction density of the negative electrode film layer is within a suitable range, which can take into account both high capacity and excellent electrolyte wetting performance on the electrode sheet, thereby helping the secondary battery to take into account high energy density as well as excellent cycle performance and storage performance.
[0009] In any embodiment, the liquid absorption rate of the negative electrode active material is 35 ml / 100 g-50 ml / 100 g.
[0010] When the negative electrode active material is within an appropriate range and the electrolyte fully infiltrates the negative electrode plate, the impact of side reactions caused by excessive surface activity of the negative electrode active material on the cycle performance and storage performance is reduced, thereby further improving the cycle performance and cycle performance of the battery and extending the service life and storage life of the battery.
[0011] In any embodiment, the tortuosity of the negative electrode plate is 2-5.
[0012] When the tortuosity of the negative electrode plate is within an appropriate range, both high capacity and excellent electrolyte wettability of the electrode plate can be achieved, thereby facilitating the secondary battery to achieve both high energy density and excellent cycle performance and storage performance.
[0013] In any embodiment, the negative electrode active material includes primary particles and secondary particles. Based on the total number of primary particles and secondary particles in the negative electrode active material, the number of the secondary particles accounts for 25%-75%, and can be optionally 26%-50%.
[0014] There are pores inside the secondary particles. The pores have a certain liquid locking ability and can lock the electrolyte that penetrates into the electrode during the cycle, which is beneficial to increase the liquid absorption rate of the negative electrode active material and facilitate the electrolyte to fully infiltrate the negative electrode. At the same time, the primary particles and secondary particles can form pores in the negative electrode film layer, which can increase the permeability of the electrolyte during the cycle and improve the cycle performance of the battery.
[0015] In any embodiment, the particle body of the negative electrode active material includes an internal region and a surface region that at least partially surrounds the internal region, and the surface region refers to a region extending 30nm from the surface of the particle body of the negative electrode active material to the interior of the particle, and the surface region includes a disordered layer. Optionally, the thickness of the disordered layer is 1nm-20nm.
[0016] The disordered layer structure in the surface area of the negative electrode active material has a large number of void structures and a certain liquid locking ability, which can increase the liquid absorption rate of the negative electrode active material, improve the wetting ability of the electrolyte to the negative electrode plate, and improve the cycle performance and storage performance of the battery.
[0017] In any embodiment, the specific surface area of the negative electrode active material is 1.1 m 2 / g-1.9m 2 / g, optional 1.2m 2 / g-1.8m 2 / g.
[0018] The specific surface area of the negative electrode active material satisfies the above range so that the liquid absorption rate of the material is within an appropriate range, so that the electrolyte can fully infiltrate the negative electrode plate during repeated lithium insertion and extraction of the negative electrode, thereby reducing the possibility of local polarization of the negative electrode plate and improving the cycle performance of the battery.
[0019] In any embodiment, the particle size distribution of the negative electrode active material (Dv90-Dv10) / Dv50 is 1.1-1.6, and can be 1.15-1.55.
[0020] The particle size distribution of the negative electrode active material meets the above range, and the tortuosity of the negative electrode plate is small, so that the electrolyte can fully infiltrate the negative electrode plate, improving the cycle performance and storage performance of the battery. At the same time, the small particle size distribution helps to improve the concentration of the particle size of the negative electrode active material, reduce the uneven distribution of active ions in the negative electrode active material caused by the large particle size difference, reduce the side reaction between the negative electrode active material with a smaller particle size and the electrolyte, and improve the cycle performance and storage performance of the secondary battery.
[0021] In any embodiment, the gram capacity of the negative electrode active material is 345 mAh / g-355 mAh / g, and can be optionally 347 mAh / g-353 mAh / g.
[0022] The gram capacity of the negative electrode active material is within an appropriate range, and its particle strength is high, which reduces the possibility of the particles tending to be flat during the cold pressing process of the electrode piece, avoids the electrolyte transmission path from becoming significantly longer, is beneficial to reducing the tortuosity of the negative electrode piece, is beneficial to the circulation of the electrolyte, and improves the cycle performance of the battery.
[0023] In any embodiment, the volume distribution particle size Dv50 of the negative electrode active material is recorded as A, and the volume distribution particle size Dv50 of the negative electrode active material after cold pressing under a pressure of 20000N is recorded as B, then the negative electrode active material satisfies: B / A≥85%, optionally ≥90%.
[0024] The bonding strength of the negative electrode active material particles that meet the above range is relatively high, which reduces the possibility of the particles tending to be flat during the cold pressing process of the electrode sheet, avoids the electrolyte transmission path from becoming significantly longer, is beneficial to reducing the tortuosity of the negative electrode sheet, facilitates the circulation of the electrolyte, and improves the cycle performance of the battery.
[0025] In any embodiment, the volume distribution particle size Dv50 of the negative electrode active material is 8.0 μm-12.0 μm.
[0026] When the volume distribution particle size Dv50 of the negative electrode active material is within an appropriate range, it is beneficial to form a reasonable pore structure between the particles of the negative electrode film layer, which is beneficial to the electrolyte infiltration of the electrode sheet and improves the cycle performance of the battery. At the same time, it can also reduce the negative impact of the excessive volume distribution particle size Dv50 of the negative electrode active material on the kinetic performance of the battery, reduce the possibility of lithium plating, and improve the cycle performance and storage performance of the battery.
[0027] In any embodiment, the surface density of the negative electrode film layer is 8 mg / cm 2 -14mg / cm 2 , optional 9mg / cm 2 -12mg / cm 2 .
[0028] The surface density of the negative electrode film layer is within an appropriate range, and the thickness of the negative electrode plate is appropriate. On the one hand, the distance for the electrolyte to laterally infiltrate the plate is relatively short, and the time required for the electrolyte to completely infiltrate the negative electrode plate is also relatively short, reducing the possibility of local polarization and improving the battery's cycle performance and storage performance. On the other hand, the surface density within an appropriate range also ensures that the battery has a certain energy density.
[0029] In any embodiment, the cohesive force of the negative electrode plate is 50 N / m-200 N / m, and can be optionally 60 N / m-150 N / m.
[0030] The negative electrode has high cohesion, which can reduce the rebound of the electrode, reduce the volume of electrolyte that needs to be replenished in the pores of the negative electrode during the cycle, reduce the time required for the electrolyte to completely infiltrate the electrode, reduce the possibility of local polarization, improve the infiltration of the electrolyte into the electrode, and improve the cycle performance and storage performance of the battery. At the same time, high cohesion also prevents the electrode from losing powder and delamination during the cycle, which has a negative impact on the cycle performance and safety performance of the battery.
[0031] In any embodiment, the rebound rate of the negative electrode plate is 8%-23%, and can be optionally 10%-21%.
[0032] The rebound rate of the negative electrode sheet will affect the volume change rate of the pores in the negative electrode sheet during the cycle, that is, the rebound rate of the negative electrode sheet will affect the volume of electrolyte that needs to be replenished in the pores of the negative electrode sheet during the cycle. If the rebound rate of the negative electrode sheet is within an appropriate range, the volume of electrolyte that needs to be replenished in the pores of the negative electrode sheet during the cycle is relatively small, so that the time required for the electrolyte to completely infiltrate the electrode sheet is relatively short, reducing the possibility of local polarization and improving the cycle performance and storage performance of the battery. At the same time, the appropriate range of the rebound rate of the negative electrode sheet also ensures that the battery has a certain energy density.
[0033] A second aspect of the present application provides an electrical device, comprising the secondary battery described in the first aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is a schematic diagram of a cross-sectional image of particles of the negative electrode active material of the present application;
[0035] Figure 2 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0036] Figure 3 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0037] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application.
[0038] Figure 5 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0039] Figure 6 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0040] Figure 7 Schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.
[0041] Description of reference numerals:
[0042] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly; 100 negative electrode active material, 101 surface area, 102 internal area. DETAILED DESCRIPTION
[0043] Below, the embodiments of the secondary battery and the electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0044] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0045] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0046] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0047] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0048] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0049] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0050] In order to improve the energy density of the battery, the compaction density of the negative electrode film layer is generally increased. However, the tortuosity of the negative electrode plate under high compaction density becomes larger, the transmission path of the electrolyte in the negative electrode film layer becomes significantly longer, and the time required for the electrolyte to infiltrate the negative electrode plate becomes longer. Some areas of the plate will not be able to absorb the discharged electrolyte in time, resulting in the inability of active ions to continue to embed into the negative electrode plate, local polarization, and uneven current distribution. Black spots appear on the surface of the negative electrode plate and are accompanied by other side reactions. The accumulation of by-products further blocks the pores, resulting in a decrease in the capacity retention rate of the battery, reducing the battery service life and storage life.
[0051] Therefore, it is difficult for current secondary batteries to have both high energy density and excellent cycle performance and storage performance.
[0052] [Negative electrode]
[0053] The present application provides a secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer comprises a negative electrode active material, and the compaction density of the negative electrode film layer is greater than or equal to 1.45 g / cm 3 The liquid absorption rate of the negative electrode active material is 30ml / 100g-60ml / 100g; the tortuosity of the negative electrode plate is less than or equal to 6.
[0054] In some embodiments, the compaction density of the negative electrode film layer can be selected to be 1.45 g / cm 3 , 1.55g / cm 3 , 1.65g / cm 3 , 1.75g / cm 3 , 1.85g / cm 3 , 1.95g / cm 3 or any value in between.
[0055] The compaction density of the negative electrode film layer can be tested by methods known in the art. As an example, an electronic balance is used to weigh a negative electrode sheet test sample with an area of S, and the weight is recorded as W1, and a micrometer is used to measure the thickness T1 of the negative electrode sheet. Then the weighed electrode sheet film layer is wiped off, the weight of the negative electrode current collector is weighed, recorded as W2, and the thickness T2 of the negative electrode current collector is measured using a micrometer. Then the compaction density of the negative electrode film layer PD = (W1-W2) / [(T1-T2)×S].
[0056] In some embodiments, the liquid absorption rate of the negative electrode active material may be 30 ml / 100 g, 35 ml / 100 g, 40 ml / 100 g, 45 ml / 100 g, 50 ml / 100 g, 55 ml / 100 g, 60 ml / 100 g or any value therebetween.
[0057] Herein, the term "liquid absorption rate of negative electrode active material" refers to the volume of electrolyte that can be absorbed by 100g of negative electrode active material. For example, a liquid absorption rate of 40ml / 100g of negative electrode active material means that 100g of negative electrode active material can absorb 40ml of electrolyte.
[0058] The liquid absorption rate of the negative electrode active material is affected by the specific surface area of the material, the proportion of secondary particles in the material and the morphology of the material.
[0059] In the present application, the liquid absorption rate of the negative electrode active material can be tested by methods known in the art. As an example, the example is as follows: obtain the test electrolyte and material sample respectively, and set the torque threshold of the tester; add the electrolyte to the sample in the mixing chamber of the tester at a constant speed. As the liquid absorption rate of the sample increases, the viscosity of the mixture of the sample and the electrolyte continues to increase. When the viscosity of the mixture reaches the preset torque threshold (for example, 1N) of the tester, stop and calculate the volume of the electrolyte absorbed by the sample per unit mass, which is the liquid absorption rate of the sample. The formula of the electrolyte: dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed in a weight ratio of 4:3:3 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L.
[0060] In some embodiments, the tortuosity of the negative electrode plate can be selected to be 1, 2, 3, 4, 5, 6 or any value therebetween.
[0061] In this article, the term "tortuosity of the negative electrode sheet" refers to the ratio of the length of the transmission path of the electrolyte through the pores of the negative electrode film layer of the negative electrode sheet to the thickness of the negative electrode film layer, which determines the diffusion path of the electrolyte inside the negative electrode film layer.
[0062] The tortuosity of the negative electrode sheet will be affected by the compaction density of the negative electrode film layer, the uniformity of the particle size of the negative electrode active material, and the particle strength.
[0063] In the present application, the tortuosity of the negative electrode plate can be tested by methods known in the art. As an example, (1) a symmetrical battery EIS test is performed: a negative electrode plate with no scratches or creases on the surface is punched into a small disc with a diameter of 14 mm. The negative electrode plates are assembled into a symmetrical battery in a glove box (humidity ≤ 1 ppm) at room temperature. After the electrolyte is injected, it is left to stand for more than 12 hours to allow the electrolyte to fully infiltrate the plate. The impedance change is detected by EIS test. The test process is: upper limit frequency 1kHZ, lower limit frequency 500mHZ, perturbation voltage 5mV, symmetrical battery voltage range -1V~1V; the test data is fitted to obtain the ion diffusion impedance Rion. The formula of the electrolyte is as follows: dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed in a weight ratio of 4:3:3 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L. (2) Calculation of the curvature of the pole piece: The area A (1.5386 cm 2 ), the thickness of the small disc d (cm), the electrolyte conductivity k, the porosity ε of the electrode, and the ion diffusion impedance Rion (Ω), are substituted into the following formula to calculate the electrode tortuosity
[0064] In the negative electrode sheet of the present application, the compaction density of the negative electrode film layer is greater than or equal to 1.45 g / cm 3 The battery has a high energy density. However, the high compaction density will increase the tortuosity of the negative electrode plate and lengthen the electrolyte transmission path, which is not conducive to the circulation of the electrolyte, affecting the wettability of the electrolyte to the negative electrode plate and affecting the cycle performance of the battery.
[0065] In order to compensate for the negative impact of high compaction density on wettability, the present application solves the problem from two aspects: shortening the wetting time and shortening the wetting path. On the one hand, a negative electrode active material with a liquid absorption rate of 30ml / 100g-60ml / 100g is used, and its liquid absorption rate will affect the diffusion ability of the electrolyte inside the electrode. If the liquid absorption rate of the negative electrode active material is too small, the wettability of the electrolyte and the negative electrode active material will be worse, and it will take longer for the electrolyte to completely infiltrate the negative electrode active material particles and the pores of the negative electrode plate, and the purpose of improving the wettability of the electrode plate will not be achieved; if the liquid absorption rate of the negative electrode active material is too large, the surface activity of the negative electrode active material is too high, which will cause it to consume more active lithium during the cycle, which is not conducive to extending the battery life. On the other hand, by regulating the uniformity of the particle size of the negative electrode active material, the particle strength or the surface density of the negative electrode film layer, the tortuosity of the electrode sheet is controlled to be less than or equal to 6, thereby compensating for the negative impact of the high compaction density on the tortuosity of the electrode sheet, and shortening the transmission path of the electrolyte in the negative electrode film layer, thereby achieving the purpose of improving the wettability of the electrolyte to the negative electrode sheet and improving the cycle performance and storage performance of the battery.
[0066] In summary, the negative electrode plate of the present application has a high compaction density, and the electrolyte can fully infiltrate the negative electrode plate during the cycle process, which can improve the cycle performance and storage performance of the battery while having a high energy density.
[0067] In some embodiments, the compaction density of the negative electrode film layer is 1.5 g / cm 3 -1.6g / cm 3 .
[0068] In some embodiments, the compaction density of the negative electrode film layer can be selected to be 1.5 g / cm 3 , 1.52g / cm 3 , 1.54g / cm 3 , 1.55g / cm 3 , 1.56g / cm 3 , 1.58g / cm 3 , 1.6g / cm 3 or any value in between.
[0069] The compaction density of the negative electrode film layer is within a suitable range, which can take into account both high capacity and excellent electrolyte wetting performance on the electrode sheet, thereby helping the secondary battery to take into account high energy density as well as excellent cycle performance and storage performance.
[0070] In some embodiments, the liquid absorption rate of the negative electrode active material is 35 ml / 100 g-50 ml / 100 g. In some embodiments, the liquid absorption rate of the negative electrode active material can be 35 ml / 100 g, 40 ml / 100 g, 45 ml / 100 g, 50 ml / 100 g or any value therebetween.
[0071] The liquid absorption rate of the negative electrode active material is within the above range. Under the premise that the electrolyte fully infiltrates the negative electrode plate, the influence of the side reactions caused by the excessive surface activity of the negative electrode active material on the cycle performance and storage performance is reduced, the cycle performance and storage performance of the battery are further improved, and the service life of the battery is extended.
[0072] In some embodiments, the tortuosity of the negative electrode plate is 2 to 5. In some embodiments, the tortuosity of the negative electrode plate can be 2, 3, 4, 5 or any value therebetween.
[0073] The tortuosity of the negative electrode sheet is within an appropriate range, which can further shorten the transmission path of the electrolyte in the negative electrode sheet, improve the wettability of the electrolyte to the negative electrode sheet, and improve the cycle performance and storage performance of the battery. At the same time, it also avoids the tortuosity being too low and controlling the compaction density or surface density of the negative electrode film layer within a relatively small range, which affects the energy density of the battery, or controlling the particle size distribution of the negative electrode active material within a small range, which increases the difficulty of material preparation and is not conducive to industrial production.
[0074] In summary, when the tortuosity of the negative electrode plate is within an appropriate range, the cycle performance and storage performance of the battery are improved while also enabling the battery to have a high energy density and / or save costs.
[0075] In some embodiments, the negative electrode active material includes primary particles and secondary particles. Based on the total number of primary particles and secondary particles in the negative electrode active material, the number of the secondary particles accounts for 25%-75%, and can be optionally 26%-50%.
[0076] In some embodiments, based on the total number of primary particles and secondary particles in the negative electrode active material, the number of secondary particles may be selected to account for 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or any value therebetween.
[0077] Herein, primary particles and secondary particles are both well-known in the art. "Primary particles" generally refer to non-agglomerated particles. "Secondary particles" refer to agglomerated particles formed by the aggregation of two or more primary particles. Agglomeration between particles can be assisted by external pressure or by another substance (e.g., a viscous chemical substance). Primary particles and secondary particles can be distinguished by using a scanning electron microscope (SEM) image.
[0078] In the present application, the number ratio of secondary particles in the negative electrode active material can be tested according to the following method: randomly select a test sample in the negative electrode film layer, randomly select multiple test areas in the test sample, use a scanning electron microscope to obtain images of the multiple test areas, and count the ratio of the number of negative electrode active material particles with secondary particle morphology in each image to the total number of negative electrode active material particles. The average value of multiple statistical results is the number ratio of secondary particles in the negative electrode active material.
[0079] The negative electrode active material of the present application includes both primary particles and secondary particles, which can take into account good cycle performance and kinetic performance. The structure of the negative electrode active material of the primary particles is relatively stable, which can effectively improve the cycle performance of the battery; the secondary particles have pores inside, which have a certain liquid locking ability, and can better absorb the electrolyte that penetrates into the pole piece during the cycle, increase the liquid absorption rate of the negative electrode active material, and facilitate the electrolyte to fully infiltrate the negative electrode pole piece, thereby improving the kinetic performance of the battery.
[0080] In some embodiments, the particle body of the negative electrode active material includes an internal region and a surface region that at least partially surrounds the internal region, and the surface region refers to a region extending 30 nm from the surface of the particle body of the negative electrode active material to the interior of the particle, and the surface region includes a disordered layer.
[0081] Figure 1 Schematic diagram of a cross-sectional image of a particle of the negative electrode active material 100 of the present application. Figure 1 As shown, the region extending 30 nm from the particle body surface of the negative electrode active material 100 to the inside is the surface region 101, and the region inside the surface region 101 is the internal region 102. The surface region 101 includes a disordered layer.
[0082] The disordered layer can be obtained through transmission electron microscopy (TEM) testing. A thin slice of about 20-50 mm thick is cut from the middle of the negative electrode active material particle body by focused ion beam (FIB), and then the thin slice is tested by TEM. It can be observed that the surface area includes lattice fringes showing long-range disorder and short-range order disordered layers, and the electron diffraction pattern at the disordered layer is halo-shaped.
[0083] The disordered layer mainly includes amorphous carbon. The disordered layer has a relatively large porous structure and a certain liquid locking ability, which can increase the liquid absorption rate of the negative electrode active material and improve the wetting ability of the electrolyte to the negative electrode plate. In addition, unlike the disordered layer coated on the surface of the negative electrode active material in the prior art, the disordered layer of the negative electrode active material provided in the embodiment of the present application is located in the particle body of the negative electrode active material, which is derived from the same raw material as the negative electrode active material and is not prepared by post-processing. Therefore, compared with the negative electrode active material obtained by surface coating treatment to obtain a disordered layer, the negative electrode active material has better material consistency, so that the battery exhibits a longer cycle life, and achieves a balance between battery kinetic performance and cycle stability, and is particularly suitable for energy storage batteries with extremely high requirements for cycle life.
[0084] In some embodiments, the thickness of the disordered layer is 1 nm to 20 nm. In some embodiments, the thickness of the disordered layer is 1 nm, 4 nm, 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 16 nm, 20 nm, or any range therebetween.
[0085] In the present application, the thickness of the disordered layer can be tested by methods known in the art. As an example, it can be obtained by transmission electron microscopy (TEM) testing. A thin slice with a thickness of about 20-50 mm is cut from the middle of the negative electrode active material particle body by a focused ion beam (FIB), and then the thin slice is subjected to a TEM test to obtain the original TEM test image, and the original image format (xx.dm3) is saved. The original image obtained by the above TEM test is opened in the Digital Micrograph software, and the disordered layer is identified by diffraction fringes or lattice spacing, and its thickness is measured. Normally, the disordered layer has no diffraction fringes, and the lattice spacing is larger than that of the ordered layer, so its thickness is measured.
[0086] The disordered layer with a thickness within the above range has a liquid absorption rate of the negative electrode active material within an appropriate range, which is beneficial for the electrolyte to fully infiltrate the negative electrode plate and improve the cycle performance of the battery; it will not cause an excessively high degree of side reaction between the active material and the electrolyte and affect the cycle performance and storage performance.
[0087] In some embodiments, the specific surface area of the negative electrode active material is 1.1 m 2 / g-1.9m 2 In some embodiments, the specific surface area of the negative electrode active material may be 1.1 m 2 / g, 1.2m 2 / g, 1.4m 2 / g, 1.6m 2 / g, 1.8m 2 / g, 1.9m 2 / g or any value therebetween.
[0088] In some embodiments, the specific surface area of the negative electrode active material is 1.2 m 2 / g-1.8m 2 In some embodiments, the specific surface area of the negative electrode active material may be 1.2 m 2 / g, 1.4m 2 / g, 1.6m 2 / g, 1.8m 2 / g or any value therebetween.
[0089] The specific surface area of the negative electrode active material is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be measured by nitrogen adsorption specific surface area analysis test method according to GB / T 19587-2017 and calculated using the BET (Brunauer Emmett Teller) method, wherein the nitrogen adsorption specific surface area analysis test can be performed using the Tri-Star 3020 specific surface area pore size analysis tester from Micromeritics, USA.
[0090] The specific surface area of the negative electrode active material satisfies the above range so that the liquid absorption rate of the material is within an appropriate range, which is beneficial for the electrolyte to fully infiltrate the negative electrode plate and improve the cycle performance of the battery; and will not cause excessive side reactions between the active material and the electrolyte to affect the cycle performance and storage performance.
[0091] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the negative electrode active material is 1.1-1.6, and can be 1.15-1.55. In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the negative electrode active material can be 1.1, 1.2, 1.3, 1.4, 1.5, 1.6 or any value therebetween.
[0092] The volume distribution particle sizes Dv10, Dv50, and Dv90 of the negative electrode active material are well known in the art, and respectively represent the particle sizes corresponding to the cumulative volume distribution percentages of the material reaching 10%, 50%, and 90%, and can be measured using instruments and methods known in the art. For example, it can be conveniently measured using a laser particle size analyzer with reference to the particle size distribution laser diffraction method of GB / T 19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0093] The particle size distribution of the negative electrode active material within the above range is helpful to improve the concentration of the particle size of the negative electrode active material, improve the concentration of the particle arrangement, reduce the tortuosity of the negative electrode plate, allow the electrolyte to fully infiltrate the negative electrode plate, improve the battery's cycle performance and storage performance, and at the same time reduce the uneven distribution of active ions in the negative electrode active material caused by the large difference in particle size, reduce the side reactions between the negative electrode active material with a smaller particle size and the electrolyte, and improve the secondary battery's cycle performance and storage performance. At the same time, the particle size distribution of the negative electrode active material is within the above range, and its particle stacking performance is good, which is conducive to improving the compaction density of the negative electrode film layer, thereby further improving the energy density of the secondary battery.
[0094] In some embodiments, the gram capacity of the negative electrode active material is 345mAh / g-355mAh / g, and can be 347mAh / g-353mAh / g. In some embodiments, the gram capacity of the negative electrode active material can be 345mAh / g, 347mAh / g, 349mAh / g, 351mAh / g, 353mAh / g, 355mAh / g or any value therebetween.
[0095] The gram capacity can be measured by any known method in the art. For example, the negative electrode active material sample and the conductive agent carbon black and polyvinylidene fluoride (PVDF) are fully stirred and mixed in an appropriate amount of solvent NMP according to a mass ratio of 91.6:1.8:6.6 to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil and dried and cold pressed; then the metal lithium sheet is used as the counter electrode and the polypropylene (PP) film is used as the isolation membrane, and the electrolyte is injected, wherein the electrolyte formula used is as follows: dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed according to a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L. CR2430 button cells are assembled in an argon-protected glove box. At 25°C, the button cell prepared above was first discharged at a constant current of 0.05C to 0.005V, then discharged at a constant current of 10μA to 0.005V, and left to stand for 5 minutes, and the first cycle discharge capacity of the button cell was recorded; then, the button cell was charged at a constant current of 0.1C to 2.0V, and the charging capacity of the button cell was recorded. The ratio of the charging capacity of the button cell to the mass of the negative electrode active material sample is the gram capacity of the negative electrode active material.
[0096] The gram capacity of the negative electrode active material is within the appropriate range, and its particle strength is high, which reduces the possibility of the particles tending to be flat during the cold pressing process of the pole piece, avoids the transmission path of the electrolyte from becoming significantly longer, is conducive to reducing the tortuosity of the negative electrode pole piece, is conducive to the circulation of the electrolyte, and improves the cycle performance and storage performance of the battery. At the same time, the appropriate gram capacity also makes the battery have a high energy density.
[0097] In some embodiments, the volume distribution particle size Dv50 of the negative electrode active material is recorded as A, and the volume distribution particle size Dv50 of the negative electrode active material after cold pressing under a pressure of 20000N is recorded as B, then the negative electrode active material satisfies: B / A≥85%, and can be optionally B / A≥90%.
[0098] As used herein, the term "volume distribution particle size Dv50" refers to the particle size corresponding to when the cumulative volume distribution number of particles reaches 50% in the particle size distribution curve.
[0099] In the present application, the volume distribution particle size Dv50 of the negative electrode active material can be tested by a method known in the art. As an example, with reference to GB / T 19077-2016, it is measured by a laser particle size analyzer. The testing instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK. The Dv50 ratio of the powder before and after cold pressing can be calculated by the ratio of the Dv50 of the powder and the Dv50 measured by scraping the powder after cold pressing of the pole piece.
[0100] In some embodiments, B / A is 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, or any range therebetween.
[0101] The bonding strength of the negative electrode active material particles that meet the above range is relatively high, which reduces the possibility of the particles tending to be flat during the cold pressing process of the electrode sheet, avoids the electrolyte transmission path from becoming significantly longer during the cold pressing process, is beneficial to reducing the tortuosity of the negative electrode sheet, facilitates the circulation of the electrolyte, and improves the battery's cycle performance and storage performance.
[0102] In some embodiments, the volume distribution particle size Dv50 of the negative electrode active material is 8.0 μm-12.0 μm.
[0103] In some embodiments, the volume distribution particle size Dv50 of the negative electrode active material may be 8.0 μm, 9.0 μm, 10.0 μm, 11.0 μm, 12.0 μm or any value therebetween.
[0104] The volume distribution particle size Dv50 of the negative electrode active material affects the gap pore size between the particles in the negative electrode film layer, and further affects the wetting channel of the electrolyte to the negative electrode plate. When the volume distribution particle size Dv50 of the negative electrode active material is within an appropriate range, it is beneficial to form a reasonable pore structure between the particles of the negative electrode film layer, which is beneficial for the electrolyte to infiltrate the plate and improve the cycle performance of the battery. At the same time, it can also reduce the negative impact of the excessive volume distribution particle size Dv50 of the negative electrode active material on the dynamic performance of the battery, reduce the possibility of lithium precipitation, and improve the cycle performance and storage performance of the battery.
[0105] In some embodiments, the surface density of the negative electrode film layer is 8 mg / cm 2 -14mg / cm 2 , optional 9mg / cm 2 -12mg / cm 2 In some embodiments, the surface density of the negative electrode film layer can be 8 mg / cm 2 , 9mg / cm 2 、10mg / cm 2 、11mg / cm 2 , 12mg / cm 2 、13mg / cm 2 、14mg / cm 2 Or any range of values in between.
[0106] The surface density of the negative electrode film layer can be tested by methods known in the art. As an example, take the cold-pressed negative electrode sheet, punch it into a small disc with an area of S1, weigh it, and record it as M1. Then wipe off the negative electrode film layer of the weighed negative electrode sheet, weigh the weight of the negative electrode current collector, and record it as M0. The surface density of the negative electrode film layer = (M1-M0) / S1.
[0107] The surface density of the negative electrode film layer is within an appropriate range. On the one hand, the distance for the electrolyte to laterally infiltrate the electrode is relatively short, the tortuosity of the electrode is small, and the time required for the electrolyte to completely infiltrate the negative electrode is also relatively short, thereby reducing the possibility of local polarization and improving the battery's cycle performance and storage performance. On the other hand, the surface density within an appropriate range also ensures that the battery has a certain energy density.
[0108] In some embodiments, the cohesive force of the negative electrode sheet is 50N / m-200N / m, and can be 60N / m-200N / m. In some embodiments, the cohesive force of the negative electrode sheet can be 50N / m, 60N / m, 70N / m, 80N / m, 90N / m, 100N / m, 110N / m, 120N / m, 130N / m, 140N / m, 150N / m, 160N / m, 170N / m, 180N / m, 190N / m, 200N / m or any value therebetween.
[0109] The cohesion of the negative electrode sheet can be tested using any method and equipment known in the art. Exemplarily, after the prepared negative electrode sheet is processed (for example, using a scraper) into a negative electrode sheet with a single-sided coating, it is cut into a long strip sample of a certain length and width (for example, the length can be 200mm and the width can be 20mm), and then the negative electrode current collector (for example, copper foil) of the sample is fixed on the aluminum plate with double-sided tape, and the side coated with the negative electrode film layer is pasted on the PTE tape; after the sample is prepared, a 180° peeling test is performed using a tensile testing machine (the peeling surface is consistent with the force line of the testing machine), the peeling speed is 50mm / min, and the force curve during the peeling process is obtained after complete peeling, and the ratio of the mean value of the force in the stable section to the width of the sample is taken as the cohesion of the negative electrode sheet. To ensure the accuracy of the test results, each negative electrode sheet sample is tested at least three times, and the average value is taken as the test result. The testing instrument can be an Instron 33652 tensile testing machine.
[0110] The negative electrode has a high cohesive force, which can reduce the rebound of the electrode, reduce the volume of electrolyte that needs to be replenished in the pores of the negative electrode during the cycle, reduce the time required for the electrolyte to completely infiltrate the electrode, reduce the possibility of local polarization, improve the infiltration of the electrolyte into the electrode, and improve the cycle performance of the battery. At the same time, the high cohesive force also reduces the impact of the powder and film removal of the electrode during the cycle on the cycle performance and safety performance of the battery.
[0111] In some embodiments, the rebound rate of the negative electrode plate is 8%-23%, and can be 10%-21%. In some embodiments, the rebound rate of the negative electrode plate can be 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 23% or any value therebetween.
[0112] In this article, the term "rebound rate of the negative electrode sheet" refers to the rate of change of the thickness of the negative electrode sheet in an empty state (the state of charge SOC is 0%) and a fully charged state (the state of charge SOC is 100%).
[0113] The rebound rate of the negative electrode sheet can be tested by any method in the art, as shown below: the thickness of the cold-pressed negative electrode sheet given in the embodiments and comparative examples of the present application is recorded as H0. Take the secondary battery given in the embodiments and comparative examples of the present application, and perform a charge and discharge test in an environment of 25°C, and discharge it to 2.5V at a constant current of 1.0C (i.e., the current value of the theoretical capacity is completely discharged within 1h). Then, charge it to 3.65V at a constant current at a charging current of 1.0C, continue to charge it at a constant voltage until the current is 0.05C, let the fully charged battery stand for 5 minutes, and then discharge it to 2.5V at a constant current at a discharge current of 1.0C. The discharge capacity at this time is recorded as C0. Charge the secondary battery to 3.65V at 25°C, disassemble the secondary battery and test the thickness of the negative electrode sheet at this time, which is recorded as H1. The rebound rate of the negative electrode sheet is: (H1 / H0-1)×100%.
[0114] The rebound rate of the negative electrode plate is related to the gram capacity of the negative electrode active material and the cohesive force of the plate.
[0115] The rebound rate of the negative electrode sheet affects the volume change rate of the pores in the negative electrode film layer during the battery cycle, that is, the volume of electrolyte that needs to be replenished in the pores. The greater the rebound rate of the negative electrode sheet, the more electrolyte needs to be removed when the battery is fully charged, and the longer it takes for the electrolyte to re-infiltrate the negative electrode sheet. The electrolyte may not be able to completely infiltrate the sheet during the cycle, affecting the battery's cycle performance. At the same time, a large sheet rebound rate leads to greater stress on the negative electrode sheet during the charge and discharge process, and a greater degree of damage to the SEI film of the negative electrode sheet. More active lithium needs to be consumed to repair during the cycle, which will also affect the battery's cycle performance and storage performance. If the rebound rate of the negative electrode sheet is too small, it is necessary to adjust the gram capacity of the negative electrode active material to a too small range or the cohesion of the negative electrode sheet to a too large range, which is not conducive to improving the battery's energy density.
[0116] In some embodiments, the negative electrode active material includes a graphite material.
[0117] The second aspect of the present application provides a method for preparing a negative electrode active material, comprising the following steps: providing raw materials; processing the raw materials to obtain an intermediate product; graphitizing the intermediate product to obtain a negative electrode active material; the particle body of the negative electrode active material includes an internal region and a surface region that at least partially surrounds the internal region, the surface region refers to a region extending 30 nm from the surface of the particle body of the negative electrode active material to the interior of the particle, and the surface region includes a disordered layer.
[0118] Herein, the term "graphitization treatment" refers to the high temperature heat treatment process of carbon materials, which is the process in which the carbon materials transform from a two-dimensional carbon network structure to a three-dimensional ordered structure through "microcrystal" growth under high temperature.
[0119] In some embodiments, the maximum power of the graphitization process is 70%-90% of the rated power of the graphitization process equipment.
[0120] In some embodiments, the maximum power of the graphitization treatment can be selected as 70%, 75%, 80%, 85%, 90% or any numerical range therebetween of the rated power of the graphitization treatment equipment. It is understood that the graphitization treatment device refers to any device capable of performing graphitization treatment, including but not limited to Acheson furnace, box furnace, inner series furnace, continuous graphitization, electric calcining furnace, medium frequency furnace, tubular furnace and other devices. Among them, the rated power of graphitization treatment equipment produced by different manufacturers may be different, and can be selected according to actual conditions. The maximum power of the graphitization treatment used in this application needs to be lower than the rated power of the graphitization treatment device to achieve uniformity of the thermal field during the graphitization treatment process.
[0121] In some embodiments, the graphitization treatment equipment is an inner series furnace, and the rated power of the inner series furnace is 25000-32000W.
[0122] In some embodiments, the graphitization treatment equipment is an Acheson furnace, and the rated power of the Acheson furnace is 28000-30000W.
[0123] In some embodiments, the graphitization process is performed at maximum power for a period of 10 h to 50 h.
[0124] In some embodiments, the time of the graphitization treatment at maximum power is 10 h, 13 h, 16 h, 19 h, 22 h, 25 h, 28 h, 31 h, 33 h, 36 h, 39 h, 42 h, 45 h, 48 h, 50 h, or any range therebetween.
[0125] In some embodiments, the graphitization treatment equipment is an internal series furnace, and the graphitization treatment time at maximum power is 10h-30h.
[0126] In some embodiments, the graphitization treatment equipment is an Acheson furnace, and the graphitization treatment time at maximum power is 30h-50h.
[0127] In some embodiments, the temperature of the graphitization treatment is 2600°C to 3000°C.
[0128] In some embodiments, the temperature of the graphitization treatment is 2600° C., 2700° C., 2800° C., 2900° C., 3000° C., or any range therebetween.
[0129] The appropriate graphitization treatment temperature and the appropriate graphitization treatment time are not likely to cause excessive rearrangement of the precursor, resulting in a high specific surface area of the graphite negative electrode active material after graphitization, which affects the high-temperature performance; it can also effectively improve the graphitization degree of the graphite negative electrode active material, thereby facilitating the simultaneous improvement of the high-temperature storage and cycle life of the secondary battery.
[0130] In some embodiments, the feedstock includes at least one of petroleum coke, needle coke, and asphalt coke, and needle coke may be selected.
[0131] As used herein, the term "petroleum coke" refers to coke formed by high-temperature carbonization of petroleum residue or petroleum asphalt.
[0132] As used herein, the term "needle coke" refers to coal tar pitch or petroleum pitch, which, after undergoing liquid phase carbonization to generate an anisotropic mesophase, can generate coke with a needle-like texture after undergoing processes such as high-temperature carbonization.
[0133] As used herein, the term "pitch coke" refers to a solid material produced by carbonizing coal tar pitch at high temperatures.
[0134] Among them, needle coke has a series of advantages such as low thermal expansion coefficient, low porosity, low sulfur, low ash, low metal content, high conductivity and easy graphitization. The graphite negative electrode active material after graphitization can achieve a high ultimate compaction density and has a low cycle expansion rate.
[0135] In some embodiments, based on the total volume of the raw material structure, the volume proportion of the fiber-type structure in the raw material is greater than or equal to 55%, and can be optionally 58%-70%.
[0136] In this article, "fibrous structure" is also called streamlined structure, which refers to the structure of the raw material with obvious fibrous texture observed under a microscope.
[0137] Generally, according to the morphological characteristics and isochromatic zone size of the raw material under a polarizing microscope, its microstructure can be divided into mosaic type, regional type and fiber type. Generally, isochromatic zone microstructure with a size less than 30μm is judged as mosaic type; isochromatic zone microstructure with a size greater than 30μm is judged as regional type, and anisotropic strip-shaped isochromatic zone is judged as fiber type structure.
[0138] In this application, the volume proportion of the fiber structure in the raw material can be tested by methods known in the art. As an example, take the raw material according to GB 1997-89, mix the raw material crushed to 1mm, shrink it to 40g~50g, use a square hole sieve to take 0.07mm~1.0mm grade sample 4g~5g for film making; prepare powder coke and block coke light film according to MT 116.1-86, the diameter of the powder coke light film shall not be less than 22mm, and the volume occupied by the cement shall be less than 1 / 3; place the sample on a slide with glue, flatten it, and then place it on the stage to focus, calibrate the microscope and adjust the polarizer and analyzer to make them orthogonal. Insert the azurite inspection plate (1λ) to make the field of view present the interference color of primary red; determine the step length of the moving ruler to ensure that more than 400 effective measuring points are evenly distributed, and the point spacing is 0.3~0.5mm and the line spacing is generally 0.5~0.8mm. Starting from one end of the sample, determine the type of microstructure under the intersection of the crosshairs, and divide the number of effective measuring points of the fiber-type structure optical organization by the total number of statistical testing points as the volume proportion of the fiber-type structure in the raw material.
[0139] In some embodiments, based on the total volume of the raw material structure, the volume proportion of the fibrous structure in the raw material can be selected to be 55%, 58%, 60%, 65%, 70% or any numerical range therebetween.
[0140] Raw materials with more fiber-type structures are beneficial to improving the compaction density and gram capacity of graphite negative electrode active materials, so that the graphite negative electrode active materials retain a high degree of integrity during the compaction process, and the battery has a high cycle life and good energy density; but too high a proportion of fiber-type structures will increase the cost and expansion rate of graphite negative electrode active materials and affect the kinetic performance. Raw materials with a volume proportion of fiber-type structures within the above range have both low costs and good gram capacity of graphite, and the battery cell has a kinetic window for the entire life cycle, thereby comprehensively improving the long-term cycle life and electrochemical performance of the battery.
[0141] In some embodiments, the maximum gram capacity that can be achieved by the feedstock is greater than the gram capacity of the graphite negative electrode active material.
[0142] By using high-grade raw materials and controlling the degree of graphitization so that the maximum gram capacity that the raw materials can achieve is not fully utilized, a graphite negative electrode active material including a disordered layer in the surface region is obtained, achieving a balance between battery cycle life and kinetic performance.
[0143] In some embodiments, the processing of raw materials specifically includes: crushing, shaping, and grading the raw materials to obtain a first precursor; granulating the first precursor to obtain a second precursor; and low-temperature carbonizing a mixture of the first precursor and the second precursor to obtain the intermediate product.
[0144] Crushing is the process of reducing the particle size of raw materials. The raw materials can be crushed by any mechanical device such as crusher, mechanical mill, etc.
[0145] Shaping is the process of adjusting the curvature and particle size of the raw materials.
[0146] Classification is the process of adjusting the particle size distribution of the raw material to obtain a first precursor that meets the particle size requirements. The particle size and particle size distribution of the first precursor can be controlled by adjusting the classification frequency and the air intake volume.
[0147] It can be understood that low-temperature carbonization of the first precursor and the second precursor to obtain the intermediate product includes both low-temperature carbonization of a mixture of the first precursor and the second precursor to obtain the intermediate product and low-temperature carbonization of the first precursor and the second precursor separately to obtain the first intermediate product and the second intermediate product respectively.
[0148] In some embodiments, the Dv50 particle size of the first precursor is 6.0 μm to 10.0 μm.
[0149] In some embodiments, the Dv50 particle size of the first precursor is 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm, 10.0 μm, or any range therebetween.
[0150] In some embodiments, the particle size distribution of the first precursor (Dv90-Dv10) / Dv50 is 1.05-1.75.
[0151] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the first precursor is 1.05, 1.15, 1.25, 1.35, 1.45, 1.55, 1.65, 1.75 or any range therebetween.
[0152] In some embodiments, the tap density of the first precursor is 0.5 g / cm3 to 0.7 g / cm3.
[0153] As used herein, the term "tapped density" refers to the mass per unit volume of powder in a container measured after being tapped under specified conditions.
[0154] In the present application, the tap density of the first precursor can be tested by a method known in the art. As an example, GB / T 5162-2006 can be referred to and a powder tap density tester can be used for measurement. The test instrument can be Dandong Better BT-301, and the test parameters are as follows: vibration frequency 250±15 times / minute, amplitude 3±0.2mm, vibration number 5000 times, and measuring cylinder 25mL.
[0155] In some embodiments, the tap density of the first precursor is 0.5 g / cm3, 0.55 g / cm3, 0.6 g / cm3, 0.65 g / cm3, 0.7 g / cm3, or any range therebetween.
[0156] In some embodiments, the Dv50 particle size of the second precursor is 11.0 μm to 15.0 μm.
[0157] In some embodiments, the Dv50 particle size of the second precursor is 11.0 μm, 12.0 μm, 13.0 μm, 14.0 μm, 15.0 μm, or any range therebetween.
[0158] The second precursor is obtained by granulating the first precursor, and therefore, the second precursor mainly forms secondary particles in the graphite negative electrode active material.
[0159] Controlling the particle sizes of the first precursor and the second precursor helps to regulate the particle size and particle size distribution of the graphite negative electrode active material and improve the cycle stability of the battery.
[0160] In some embodiments, the crushing, shaping, and grading of the raw materials to obtain the first precursor includes: crushing, shaping, and grading the raw materials to obtain secondary raw materials; removing fine powder accounting for 10%-35% of the total mass of the secondary raw materials to obtain the first precursor; the Dv50 of the fine powder is 3μm-7μm and Dv99 is less than or equal to 30μm, and the particle size distribution of the fine powder (Dv90-Dv10) / Dv50 is greater than 1.6.
[0161] In some embodiments, the temperature of low temperature carbonization is 900° C.-1300° C., and the time of low temperature carbonization is 24 h-240 h.
[0162] In some embodiments, the temperature of the low temperature carbonization may be selected to be 900° C., 1000° C., 1100° C., 1200° C., 1300° C., or any range therebetween.
[0163] In some embodiments, the low-temperature carbonization time may be 24 h, 50 h, 75 h, 100 h, 150 h, 200 h, 240 h, or any range therebetween.
[0164] In some embodiments, the first intermediate product is graphitized to obtain primary particles.
[0165] In some embodiments, the second intermediate product is graphitized to obtain secondary particles.
[0166] In some embodiments, the primary particles and the secondary particles are mixed at a mass ratio of 3:7-7:3 to obtain the negative electrode active material.
[0167] In some embodiments, the first intermediate product and the second intermediate product are mixed at a mass ratio of 3:7-7:3 to obtain an intermediate product, and the intermediate product is graphitized to obtain the negative electrode active material.
[0168] In some embodiments, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0169] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0170] In some embodiments, the negative electrode film layer may also be one or more of conventional natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material. The tin-based material may include one or more of elemental tin, tin oxide and tin alloy material.
[0171] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0172] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0173] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0174] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0175] In one embodiment of the present application, a secondary battery is provided.
[0176] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0177] [Positive electrode]
[0178] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.
[0179] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0180] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0181] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0182] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0183] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0184] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0185] [Electrolytes]
[0186] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0187] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0188] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0189] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0190] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0191] [Isolation film]
[0192] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0193] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0194] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0195] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0196] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0197] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 2 The secondary battery 5 is a square structure as an example.
[0198] In some embodiments, reference Figure 3 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0199] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0200] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0201] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0202] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0203] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0204] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0205] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0206] Figure 7 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0207] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0208] Example
[0209] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0210] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0211] 1. Preparation method
[0212] Preparation of negative electrode active materials H1-H6
[0213] H1: The needle coke with a fiber structure volume ratio of 61.1% is coarsely crushed, and then the coarsely crushed material is crushed and sieved, and the sieved material is shaped and graded. During the grading process, a certain amount of fine powder is removed to obtain the first precursor, and 21% of the fine powder relative to the total mass of the sieved material is removed. The fine powder refers to particles with a Dv50 particle size of 3-7μm and a particle size distribution of (Dv90-Dv10) / Dv50>1.6. Among them, the Dv50 particle size of the first precursor is 9.0μm, the particle size distribution (Dv90-Dv10) / Dv50 is 1.35, and the tap density of the first precursor is 0.65g / cm 3 .
[0214] The first precursor is granulated and shaped in a reaction kettle to obtain a second precursor with a particle size Dv50 of 14.3 μm;
[0215] The first precursor and the second precursor were placed in a kiln for carbonization at a carbonization temperature of 1100°C and a high temperature zone time of 24 hours to obtain a first intermediate product and a second intermediate product. The tap density of the first intermediate product was 0.98 g / cm 3 The tap density of the second intermediate product is 0.91 g / cm 3 ;
[0216] The first intermediate product and the second intermediate product are graphitized at a temperature of 2800°C, respectively. The graphitization treatment device is an internal series furnace with a rated power of 28000W. The maximum power of the graphitization treatment is 22400W, maximum power / rated power×100%=80%, and the constant power time of the maximum power is maintained for 20h to obtain primary particles and secondary particles, respectively.
[0217] The primary particles and the secondary particles were uniformly mixed in a mass ratio of 30%:70%, and the final negative electrode active material H1 was obtained after sieving.
[0218] The preparation process of negative electrode active materials H2-H6 is basically the same as that of negative electrode active material H1, and the adjusted parameters are shown in Table 1.
[0219] Table 1
[0220]
[0221] Example 1
[0222] 1) Preparation of negative electrode sheet
[0223] The prepared negative electrode active material H1, conductive agent carbon black Super P, thickener sodium carboxymethyl cellulose, and binder styrene butadiene rubber were mixed in a mass ratio of 96:1:1.2:1.8, and deionized water was added as a solvent. The mixture was stirred under the action of a vacuum mixer until the system was uniform to obtain a negative electrode slurry. The negative electrode slurry was evenly coated on the negative electrode current collector copper foil, and the negative electrode sheet was obtained after drying, cold pressing, and cutting. The compaction density of the negative electrode film layer is 1.55g / cm 3 , surface density is 9.2mg / cm 2 .
[0224] 2) Preparation of positive electrode
[0225] The positive electrode active material lithium iron phosphate (LFP), the conductive agent Super P, and the binder polyvinylidene fluoride are mixed in a mass ratio of 97:1:2, and the solvent N-methylpyrrolidone is added. The system is stirred under the action of a vacuum mixer until it becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying, cold pressing, and cutting. The compaction density of the positive electrode film layer is 2.50g / cm 3 , surface density is 19.7mg / cm 2 .
[0226] 3) Preparation of electrolyte
[0227] In an argon atmosphere glove box with a water content of <10ppm, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed in a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L, and then vinylene carbonate (VC) is added, and the content of VC is 2% of the total mass of the electrolyte.
[0228] 4) Isolation film
[0229] Polypropylene film is used as the isolation film.
[0230] 5) Preparation of secondary batteries
[0231] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play a role of isolation, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery embodiment is obtained.
[0232] Examples 2-8 and Comparative Examples 1-3
[0233] The preparation method of the secondary battery is similar to that of Example 1, except that different negative electrode active materials are used and the surface density or compaction density of the negative electrode film layer is adjusted, as shown in Table 2 for details.
[0234] 2. Performance Test
[0235] 1. Cycle performance test of secondary battery at 60℃
[0236] At 60°C, the batteries of the above embodiments and comparative examples were charged at a constant current of 1C to a voltage of 3.65V, then charged at a constant voltage of 3.65V to a current ≤ 0.05C, and then discharged at a constant current of 1C to a voltage of 2.5V. This was a charge and discharge process, and the discharge capacity C1 of the first cycle was recorded. The charge and discharge cycles were repeated until the battery capacity decayed to 80% of the initial capacity C1, and the test was stopped, and the number of cycle tests was recorded.
[0237] 2. Storage performance of secondary batteries at room temperature
[0238] In an environment of 25°C, the charge and discharge test was carried out, charging at a constant current of 1C to a voltage of 3.65V, then charging at a constant voltage of 3.65V to a current ≤0.05C, and then discharging the battery at a constant current of 1C to a voltage of 2.5V. This is a charge and discharge process, and the discharge capacity of the first cycle is recorded, which is the initial discharge capacity, recorded as C0. Then the fully charged battery cell is placed in an environment of 60°C for different periods of time, and the remaining capacity C1 is tested at 25°C every 30 days. This is a storage cycle, and the discharge capacity this time is the discharge capacity after the first storage. Subsequently, the first storage test process is repeated, the discharge capacity value during the storage process is recorded, and the 120-day cycle capacity retention rate is recorded.
[0239] 3. Results
[0240] Table 2
[0241]
[0242] From the comparison between Examples 1-8 and Comparative Examples 1-3, it can be seen that the embodiments of the present application simultaneously meet the requirement that the compaction density of the negative electrode film layer is greater than or equal to 1.45 g / cm 3 The liquid absorption rate of the negative electrode active materials H1-H4 is 30ml / 100g-60ml / 100g, and the tortuosity of the negative electrode sheet is less than or equal to 6. The secondary battery can have good cycle performance and storage performance while having a higher energy density.
[0243] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A secondary battery, comprising a negative electrode plate, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer comprises a negative electrode active material, and the compaction density of the negative electrode film layer is greater than or equal to 1.45 g / cm 3 The liquid absorption rate of the negative electrode active material is 30ml / 100g-60ml / 100g, and the tortuosity of the negative electrode plate is less than or equal to 6.
2. The secondary battery according to claim 1, characterized in that: The compaction density of the negative electrode film layer is 1.5 g / cm 3 -1.6g / cm 3 .
3. The secondary battery according to claim 1 or 2, characterized in that: The liquid absorption rate of the negative electrode active material is 35ml / 100g-50ml / 100g.
4. The secondary battery according to any one of claims 1 to 3, characterized in that: The tortuosity of the negative electrode plate is 2-5.
5. The secondary battery according to claim 1, characterized in that: The negative electrode active material includes both primary particles and secondary particles; optionally, based on the total number of primary particles and secondary particles in the negative electrode active material, the number of the secondary particles accounts for 25%-75%, and optionally 26%-50%.
6. The secondary battery according to any one of claims 1 to 5, characterized in that: The particle body of the negative electrode active material includes an internal region and a surface region that at least partially surrounds the internal region, wherein the surface region refers to a region extending 30 nm from the surface of the particle body of the negative electrode active material to the interior of the particle, and the surface region includes a disordered layer. Optionally, the thickness of the disordered layer is 1 nm-20 nm.
7. The secondary battery according to any one of claims 1 to 6, characterized in that: The specific surface area of the negative electrode active material is 1.1 m 2 / g-1.9m 2 / g, optional 1.2m 2 / g-1.8m 2 / g.
8. The secondary battery according to any one of claims 1 to 7, characterized in that: The particle size distribution of the negative electrode active material (Dv90-Dv10) / Dv50 is 1.1-1.6, and can be optionally 1.15-1.
55.
9. The secondary battery according to any one of claims 1 to 8, characterized in that: The gram capacity of the negative electrode active material is 345 mAh / g-355 mAh / g, and can be optionally 347 mAh / g-353 mAh / g.
10. The secondary battery according to any one of claims 1 to 9, characterized in that: The volume distribution particle size Dv50 of the negative electrode active material is recorded as A, and the volume distribution particle size Dv50 of the negative electrode active material after cold pressing under a pressure of 20000N is recorded as B. Then the negative electrode active material satisfies: B / A≥85%, and can be optionally ≥90%.
11. The secondary battery according to any one of claims 1 to 10, characterized in that: The volume distribution particle size Dv50 of the negative electrode active material is 8.0 μm-12.0 μm.
12. The secondary battery according to any one of claims 1 to 11, characterized in that: The surface density of the negative electrode film layer is 8 mg / cm 2 -14mg / cm 2 , optional 9mg / cm 2 -12mg / cm 2 .
13. The secondary battery according to any one of claims 1 to 12, characterized in that: The cohesive force of the negative electrode plate is 50N / m-200N / m, and can be optionally 60N / m-150N / m.
14. The secondary battery according to any one of claims 1 to 13, characterized in that: The rebound rate of the negative electrode plate is 8%-23%, and can be optionally 10%-21%.
15. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 14.
Citation Information
Patent Citations
Lithium ion battery cathode and lithium ion battery
CN103326027A
Electrode material and secondary battery
CN109461934A
Electrochemical device and electronic device
CN113424348A
Negative pole piece and secondary battery
CN116364848A
Graphite negative electrode material with high electrolyte compatibility and preparation method thereof
CN116598486A